Standardized Clinical Protocols to Promote Maternal Safety. Issue 2 (March 2018) - N/A,
Abstract : There is an abundance of evidence-based resources to promote patient safety in maternity care which are available at no cost. Various patient safety resources are discussed including those from Council on Patient Safety in Women's Health Care, the Centers for Disease Control and Prevention, and the California Maternal Quality Care Collaborative.